Дослідження методів масштабування ознак для передачі даних через брокери повідомлень таких як RabbitMQ та Kafka - Рамазанов, Р. Ш. (ХНУРЕ, 2024)
This study delves into the exploration of traditional feature scaling methods within the context of RabbitMQ and Kafka message brokers. It meticulously examines vertical, horizontal, and sharding scaling techniques, highlighting their respective advantages and limitations in enhancing the efficiency and reliability of data transmission in microservices architectures. Through an in-depth analysis, it evaluates the applicability of these methods in optimizing the performance of RabbitMQ and Kafka, crucial components for facilitating communication among various system elements. Furthermore, the study discusses optimization possibilities, emphasizing the importance of a nuanced approach tailored to specific system requirements.
Keywords: масштабування; брокер повідомлень; RabbitMQ; Kafka